Security of IT based learning systems - Bierhahn, H.-U. (International Journal of Computer Science in Sport, 2002)
IT security incidents are increasing nearly exponentially. With this increase, the importance of data accessibility, confidentiality, integrity, and authenticity grows. IT-based learning systems are especially endangered through intentional destructive actions. A basic condition to guarantee the security of personal data is the compliance with national laws and international regulations, especially the data protection laws. Furthermore, the complex standards of the BSI baseline protection manual must be fulfilled to avoid intentional destructive actions against the IT systems.